Impact of surface roughness of diamond coatings on the cutting performance when dry machining of graphite. (21st July 2008) - Cabral, Gil; Reis, P.; Titus, E.; Madaleno, J.C.; Davim, J.P.; Gracio, J.; Ahmed, Waqar; Jackson, Mark
Time Modulated Chemical Vapour Deposition (TMCVD) process regime has been used to deposit diamond coatings onto commercially available tungsten carbide tool inserts. The TMCVD process was developed in our laboratories so that diamond films with fine grains could be deposited. It accomplishes this by promoting secondary nucleation during larger methane flow modulations. The average surface roughness of the diamond coatings were correlated with the cutting performance of the coatings when dry machining of graphite. Inserts coated were characterised by Scanning Electron Microscopy (SEM) and Raman spectroscopy and were tested for turning performance using graphite as the workpiece material. The cutting forces were measured by the DynoWareT™ data acquisition system. Polycrystalline Diamond (PCD) inserts were also used for comparison. Repeated turning tests showed that the surface roughness of the coatings is a limiting factor when achieving better chip flow during machining.